2010
DOI: 10.1515/cclm.2010.066
|View full text |Cite
|
Sign up to set email alerts
|

Soluble mesothelin related peptides (SMRP) and osteopontin as protein biomarkers for malignant mesothelioma: analytical validation of ELISA based assays and characterization at mRNA and protein levels

Abstract: Background: There is a need to identify reliable markers for malignant mesothelioma. Soluble mesothelin related peptides (SMRP) and osteopontin (OPN) have gained interest in recent years for this purpose. Methods: SMRP (Fujirebio Diagnostics Inc.) and OPN (R&D Inc.) ELISA methods were evaluated for multiple parameters. Concentrations were measured in blood from patients with mesothelioma, normal healthy volunteers, and patients with other (non-mesothelioma) cancers. In silico analysis was performed using the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Other authors confirmed OPN as an effective marker for MPM diagnosis (22,(25)(26)(27)(28) and the utility as biological markers for the health surveillance of past-exposed patients (28). Nevertheless, further studies with a larger sample size and better design are needed to carefully assess the diagnostic power of this biomarker (25).…”
Section: Osteopontin (Opn)mentioning
confidence: 84%
“…Other authors confirmed OPN as an effective marker for MPM diagnosis (22,(25)(26)(27)(28) and the utility as biological markers for the health surveillance of past-exposed patients (28). Nevertheless, further studies with a larger sample size and better design are needed to carefully assess the diagnostic power of this biomarker (25).…”
Section: Osteopontin (Opn)mentioning
confidence: 84%
“…However, the specific role of OPN in the pathogenesis of MPM still remains unclear. Unlike SMRP and MPF, OPN concentrations do not show any consistent directional change in post-surgical samples [21,40], suggesting no connection with tumor bulk. It was observed in an analysis of 91 patients that serum OPN assayed by ELISA with a 350-ng/mL cutoff remained as a negative prognostic factor for patients' survival in the univariate and multivariate model, which could be explained by the role of elevated OPN level in stimulating tumor growth and spread [23].…”
Section: Opnmentioning
confidence: 86%
“…These findings are consistent with those first reported by Robinson et al (36), suggesting that the use of serum SMRP levels for diagnosing MM has excellent universality and reproducibility. Based on previous studies, including our own, SMRP is considered to be a highly specific biomarker for MM; however, its sensitivity, ranging from 48-80%, is moderate (9,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(27)(28)(29)(30)(31)(32)(33)(34)(35). To improve the performance of SMRP in diagnosing MM, there is a need to increase the sensitivity while maintaining a high degree of specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the advances in imaging studies and endoscopic examinations, the development of biomarkers useful for serum or effusion diagnosis is crucial for the early diagnosis of MM. Currently known biomarkers for diagnosing MM include cytokeratin 19 fragment (CYFRA) (5-7), tissue polypeptide antigen (TPA) (5,6,8), hyaluronic acid (8), carbohydrate antigen (CA125) (8,9) and osteopontin (10)(11)(12)(13)(14)(15). However, these markers have low specificity for MM.…”
Section: Introductionmentioning
confidence: 99%